Інноваційні технології ХХІ століття. Вип. 2 - Хмельницький інститут ПрАТ «ВНЗ «МАУП» (My University, 2017)
У збірнику наукових праць «Інноваційні технології ХХІ століття» представлено узагальнені тези доповідей та виступів учасників засідання круглого столу «Інноваційні технології як основа професійного становлення особистості». Авторами статей розкрито широке коло актуальних проблем: майбутнє України в інформаційному просторі; комп’ютерні науки в контексті інноваційного розвитку українського суспільства; історичні, правові, економічні, філологічні, педагогічні науки в контексті інноваційного розвитку України; інноваційні технології у ході розвитку освітньої галузі: проблеми та перспективи. The collection of scientific papers “Innovative Technologies of the 21st Century” presents generalized theses of reports and speeches of the participants of the round table meeting “Innovative Technologies as the Basis of Professional Development of the Individual”. The authors of the articles have revealed a wide range of topical problems: the future of Ukraine in the information space; computer science in the context of innovative development of Ukrainian society; historical, legal, economic, philological, pedagogical sciences in the context of innovative development of Ukraine; innovative technologies in the course of development of the educational sector: problems and prospects.